Faculty of Dentistry, Kuwait University, Designated as a World Health Organization Collaborating Centre for Primary Oral Health Care - Behbehani, J.M. (Med Princ Pract, 2014)
The Faculty of Dentistry, Kuwait University, was designated as a World Health Organization (WHO) Collaborating Centre for Primary Oral Health Care (POHC) in 2011. This article aimed to describe the following: (1) the background for this nomination, (2) the WHO Collaborating Centre for POHC, its terms of reference and 5 activities, (3) the primary health care concept as it was established in Alma-Ata, (4) the oral health situation in Kuwait and in the Middle-East region and, finally, (5) how POHC policy should be implemented in Kuwait and this region. It can be concluded that, because the caries experience is very high in Kuwait and in the other countries of the Eastern Mediterranean region, good POHC programmes should be designed and implemented in this region. The Faculty of Dentistry will strengthen its research tradition and as a WHO Collaborating Centre for POHC will try to collect information and experience from POHC in this region and exchange ideas between POHC experts in this region on how these programmes could be further developed. This will happen according to the terms of reference and activity plans of the WHO Collaborating Centre for POHC approved by the WHO Global Oral Health Programme.